Association between interatrial block, left atrial fibrosis, and mechanical dyssynchrony: Electrocardiography‐magnetic resonance imaging correlation. (15th June 2020) - Ciuffo, Luisa; Bruña, Vanesa; Martínez‐Sellés, Manuel; de Vasconcellos, Henrique Doria; Tao, Susumu; Zghaib, Tarek; Nazarian, Saman; Spragg, David D.; Marine, Joseph; Berger, Ronald D.; Lima, Joao A. C.; Calkins, Hugh; et al.
Abstract: Introduction: Advanced interatrial block (IAB) on a 12‐lead electrocardiogram (ECG) is a predictor of stroke, incident atrial fibrillation (AF), and AF recurrence after catheter ablation. The objective of this study was to determine which features of IAB structural remodeling is associated with left atrium (LA) magnetic resonance imaging structure and function. Methods/Results: We included 152 consecutive patients (23% nonparoxysmal AF) who underwent preprocedural ECG and cardiac magnetic resonance (CMR) in sinus rhythm before catheter ablation of AF. IAB was defined as P‐wave duration ≥120 ms, and was considered partial if P‐wave was positive and advanced if P‐wave had a biphasic morphology in inferior leads. From cine CMR and late gadolinium enhancement, we derived LA maximum and minimum volume indices, strain, LA fibrosis, and LA dyssynchrony. A total of 77 patients (50.7% paroxysmal) had normal P‐wave, 52 (34.2%) partial IAB, and 23 (15.1%) advanced IAB. Patients with advanced IAB had significantly higher LA minimum volume index (25.7 vs 19.9 mL/m 2, P  = .010), more LA fibrosis (21.9% vs 13.1%, P  = .020), and lower LA maximum strain rate (0.99 vs 1.18, P  = .007) than those without. Advanced IAB was independently associated with LA (minimum [ P  = .032] and fibrosis [ P  = .009]). P‐wave duration was also independently associated with LA fibrosis ( β  = .33; P  = .049) and LA mechanical dyssynchrony ( β  = 2.01; P  = .007). Conclusion: Advanced IAB is associated with larger LA volumes, lower emptying fraction, and more fibrosis. Longer P‐wave duration is also associated with more LA fibrosis and higher LA mechanical dyssynchrony.